(3GdeMUd ef fgGjI GdYbhd aj Yde GdCUhds - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3eMeO Hf KGHJ Hf SYjO GdhQjfdGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdeJYGdi HLdGd CMOjKJg CeG HYO abO EdJeS efi LeY ef CaGVd GdYdeGA Cf CUfa dge eNJUQkG ai Ydei GdcdGe hCUhd Gdabg aUfaJ dge gPG GdeNJUQ , hSejJg GdeMUd s
(3BNQgG (B:s
(3hGdKGfjI GdJbjI , acdeG CQGOhG TjFkG JcdhG Hg , aEPG bjd dge (B: (3gPG NWC Ch XgQ dge HdWGfg bGdhG (B: (3EfeG bdfGg JbjI hGddg CYde fLR GdcJGH GdeMUd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1615s
Keywords: (3CUhd Gdabgs